Control of diseases of Phaseolus vulgaris L. in central Africa using cultural methods - Trutmann, P.; Kaytare, J. (1986)
The effect of seed selection methods and removal of diseased seedlings and leaves on bean disease development and yield was studied. The best results were obtained with the removal of diseased leaves, and the combined use of diseased seedling removal plus removal of diseased leaves significantly (P = 0.05) increased yields by 67 and 43 percent, resp. (CIAT)